2004
DOI: 10.1111/j.1471-4159.2004.02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Nogo‐66 and myelin‐associated glycoprotein (MAG) inhibit the adhesion and migration of Nogo‐66 receptor expressing human glioma cells

Abstract: Malignant gliomas are common and aggressive brain tumours associated with significant morbidity and mortality. We showed in this report that substratum adherence and migration by human U87MG glioma cells in culture were significantly attenuated by the extracellular domains of Nogo-A (Nogo-66) and the myelin-associated glycoprotein (MAG). U87MG cells contained significant amounts of endogenous Nogo-66 receptor (NgR), and treatment of the cells with phosphatidylinositol-specific phospholipase C (PI-PLC) or NgR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 15 publications
1
36
0
2
Order By: Relevance
“…Liao H et al [9] showed that the substratum adherence and migration of human U87MG glioma cells in culture were significantly attenuated by the extracellular domain of Nogo-A (Nogo-66) and the myelin-associated glycoprotein (MAG). U87MG cells contained large amounts of endogenous Nogo-66 receptors (NgRs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liao H et al [9] showed that the substratum adherence and migration of human U87MG glioma cells in culture were significantly attenuated by the extracellular domain of Nogo-A (Nogo-66) and the myelin-associated glycoprotein (MAG). U87MG cells contained large amounts of endogenous Nogo-66 receptors (NgRs).…”
Section: Discussionmentioning
confidence: 99%
“…Liao H et al [9] reported that the substratum adherence and migration of human U87MG glioma cells in the culture were significantly attenuated by the extracellular domains of Nogo-A, indicating that Nogo-A can modulate glioma growth and migration. However, Teng FY et al [14] hypothesized that Nogo isoforms might have the antitumorigenic or tumorsuppressing activity.…”
Section: Introductionmentioning
confidence: 99%
“…Like other members of the reticulon family, Nogo is an endoplasmic reticulum-enriched protein, and interactions with other endoplasmic reticulum, mitochondrial and cytoplasmic proteins may be important for various cellular physiological processes. The fact that Nogo-deficient mice apparently exhibit a normal physiological phenotype could be related to the compensatory roles that other members of the reticulon family might perform in normal physiology [31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…For instance, Nogo-A and NgR1 have been implicated in neurosphere cell proliferation (Li et al, 2011), differentiation (Wang and Zhu, 2008;Lööv et al, 2012), and control of tumor malignancy (Liao et al, 2004;Cheung et al, 2009;Xiong et al, 2012). The latter findings point to the participation of Nogo-A/NgR1 signaling in the regulation of other aspects of growth, such as tissue expansion or turnover by cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Here, neural stem cells (NSCs) with astrocytic features generate intermediate progenitors giving rise to neuroblasts that migrate to the olfactory bulb (OB) along the rostral migratory stream (RMS) (Kriegstein and Alvarez-Buylla, 2009;Ihrie and Alvarez-Buylla, 2011). Using pharmacological approaches along with in vitro and in vivo experiments, we found that Nogo-A/NgR1 signaling regulates the pace of neuronal neogeneration by reducing NSC proliferation.…”
Section: Introductionmentioning
confidence: 99%